The adequacy of legal framework regarding motor vehicle theft in Malaysia with reference to Singapore / Norhanim Idham, Athirah Abd Razak, Norfarhana Azizan - Idham, Norhanim; Abd Razak, Athirah; Azizan, Norfarhana (2011)
In Malaysia, motor vehicle theft is a one of the crime that mostly occurred and committed. There is law governing this particular offence which is provided under section 379 of the penal code but the problem still cannot be solved. Even though we have this provision, however, the said law is seems to be inadequate which causes many issues have arisen. The society started to argue that the crime is still occurred because we do not have an effective law and special clause as applied in Singapore, where their country is really strict with regards to this matter. Not only that, it is also argued that the leniency of the judge in making decision for the motor vehicle theft offender had caused the law become more ineffective. This research is to examine the law on theft of motor vehicle under Malaysia Penal Code which will focus on Section 379 with reference to the Singapore Penal Code and to study how the implementation of the section 379A regarding punishment available for motor vehicle theft which later will answer the question of whether the law is sufficient or Malaysia need to adopt such proviso in Singapore. Furthermore, this research adopts qualitative type of research therefore; a library-based research will be conducted. Information will be gathered from books, cases study, articles, journals and statistics which cover the aspect of law on theft on motor vehicle specifically. The central aim of conducting the library research is to find the definition of theft, nature, and characteristic of theft thus nairow down to the theft on motor vehicles. Moreover, this study will be governed through case studies whereby those related cases will be analyzed in order get further explanations and understandings regarding how the law itself is being enforced in Malaysia. Then, internet search will also be conducted. Online database such as Lexis-Nexis and online articles will be used to obtain information that related to this research.